Parental Engagement in Promoting Awareness of Contraceptive Use among Female Students in Nigeria and Cameroon - Adisa, Rasaq Muhammed; Masso, Fabiolla Michelle; Udende, Patrick; Sholola, Yusuf Ajani; Fahmi, Mahamood Ahmad; La'aro, Oba Abdulkadir (Al-Sihah : The Public Health Science Journal, 2023)
Despite government and non-governmental organizations' efforts, contraceptive utilization in Nigeria remains low. Similarly, Cameroon faces high maternal mortality and low contraceptive prevalence. Adolescent pregnancy remains a significant social and public health concern globally, necessitating efforts to promote contraceptive use. Parent-adolescent sexual communication is often viewed as taboo in Nigeria and Cameroon, hindering awareness about contraceptive use. This study examines the role of parents in creating awareness of contraceptive use among female university students in Nigeria and Cameroon. The study adopts a comparative approach, investigating the cultural role of parents in awareness creation for contraceptive use in Nigeria and Cameroon. A cross-sectional study was conducted among 420 female university students in both countries. The findings highlight the valuable role of parents in shaping adolescents' knowledge and behavior regarding contraceptive use. Recommendations include enhancing comprehensive sexual and reproductive health education, promoting parent-adolescent communication, addressing cultural barriers, improving contraceptive access, and conducting further research. Implementing these recommendations can empower adolescents with accurate information, foster supportive parent-adolescent relationships, and enhance sexual and reproductive health outcomes among young people.